The inspirer of technical education in Ukraine - Ponomaryov , O.; Romanovskiy , O.; Cheremsky , M. (New Collegium, 2020)
Victor Lvovich Kirpichev are distinguished scientific, engineer, teacher and reformer of higher technical school. He are founder and organizer of technical education in Ukraine. Kirpichev combined knowledge and industrial practice of student. He give much attention for creative development of personality. Kirpichev holded that engineer must have artistic education. He in every way possible supported students and defended their right to self-determination.